Formation of periodical magnetic fields by sequence of rings with different electric and magnetic properties - Kopiychenko, D.Yu.; Onishchenko, I.N.; Sotnikov, G.V.; Pushkarev, S.S.; Prokopenko, Yu.V.; Chupikov, P.T.; Medvedev, D.V. (Вопросы атомной науки и техники, 2004)
The electrodynamics analysis of topography of magnetic fields originating in spatially periodic system is carried out. The system under investigation is the solenoid inside which rings made from materials differ in electric and magnetic properties are periodically placed. The system of equations connecting amplitudes of spatial harmonics of the field is obtained. This system is parsed numerically. Requirements are determined when in the spatial structure of a magnetic field the dominating role is played by the main harmonic. The amplitudes of longitudinal and transverse components of the modulated magnetic field as a function of the ring sizes, current frequency, magnetic and electric properties of rings materials are investigated. The amplitudes of the fields obtained in the full electrodynamics consideration are compared with the amplitudes of a periodic magnetic field, obtained in an impedance approximation.